Electronic and optoelectronic properties of Al/coumarin doped Pr2Se3-Tl2Se/p-Si devices - Tataroglu, A.; Ahmedova, C.; Barim, G.; Al-Sehemi, Abdullah G.; Karabulut, Abdulkerim; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Springer, 2018)
In this study, coumarin-doped Pr2Se3-Tl2Se (0.00, 0.05, 0.1, 0.3 wt% coumarin) were covered on the front side of a p-Si substrate by drop coating method and thus Al/coumarin doped Pr2Se3-Tl2Se/p-Si diodes were fabricated. The electronic and optoelectronic properties of the prepared diodes were investigated. The highest rectification ratio (RR = I-F/I-R) value was found to be 2.24 x 10(5) for the diode having 0.05 wt% coumarin doping at dark and +/- 5 V. Also, the highest I-photo/I-dark photosensitivity was found to be 1327 for the diode which has 0.1 wt% coumarin doping at 100 mW/cm(2) and - 5 V. The photocurrent of the diodes is higher than the dark current and increases by the increase of the light intensity. These results confirm that the fabricated diodes show a strong photovoltaic behavior. The electronic parameters of the diodes, for example ideality factor and barrier height values, were calculated by the use of current-voltage characteristics. The transient measurement proves that the diodes show both photodiode and photocapacitor behaviors. The change on the conductance and capacitance by the frequency is attributed to the existence of interface states. Thus, the obtained results suggest that the prepared diodes might be used as a photosensor in the applications of optoelectronic.
Keywords: Electrical-Properties; Coumarin; Photodetector; Dependence; Interface; Frequency; State